Challenges in the implementation of Proactive Land Acquisition Strategy (PLAS) in Mopani District Area, Limpopo Province - Malatji, Thabiso Lucky (My University, 2017)
The aim of the study was to investigate elements that compromise the success of Proactive Land Acquisition Strategy (PLAS) in Mopani District, Limpopo Province. There is a general view that PLAS intended to fast track the land reform process. The emerging farmers as soon as they get the land through PLAS are expected to use the land for production so as to improve their socio- economic status and contribute to the local economic growth. The Department of Rural Development and Land Reform proactively acquires the land and redistributes it to the previously disadvantaged people in a lease contract. Emerging farmers do not need to own the land and have title deeds as the land belongs to the government. PLAS is state driven because only the government can proactively acquire the land and lease it out to prospective productive emerging farmers from previously disadvantaged groups. Qualitative research design was used to collect data. The target group in this study were direct beneficiaries of PLAS or emerging farmers. Data was collected using focus group discussions with emerging farmers and one-on-one interviews in all three local municipalities: Ba-Phalaborwa, Tzaneen and Maruleng. One- on- one interviews were conducted with the key participants from the Department of Rural Development and Land Reform and the Limpopo Department of Agriculture. The results of the study show that the emerging farmers are not effectively using the land as expected. They do not have the necessary support from government or Department of Rural Development and Land Reform. It was also revealed in the study that the Limpopo Department of Agriculture is expected to support the emerging farmers with technical support. In practice there is no visible form of support from the provincial department and farmers are left to fend for themselves. Emerging farmers usually lack farming skills and need regular training and support to be able to continue with their farming and businesses. The findings further reveal that the emerging farmers face serious challenges such as a lack of funding, water shortage, and lack of access to markets and their recapitalisation is reduced. These findings show that the strategy is not responsive enough because of lack of resources from the government. While there are instances where the white farmers are willing to sell their land, the government do not always have resources to acquire such lands. Also most of these land prices are often inflated and it is where these sellers are taking advantage of the government. This study recommends that the government should support the emerging farmers by all means possible. That will lead to profitable farming and the lives of the people will change qualitatively, leading to social and economic development. It is recommended further that the emerging farmers be given appropriate training so that they can be equipped with skills and be able to run and manage their farms
Thesis (MPA.) -- University of Limpopo, 2017.
Keywords: Proactive Land Acquisition Strategy; Mopani District; Limpopo Province; Land reform; Land reform - South Africa.; Land reform beneficiaries